1996
DOI: 10.1021/jo951482d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 2,3,4-Trisubstituted Piperidines by a Formal Hetero-Ene Reaction of Amino Acid Derivatives

Abstract: N-Benzyl- or N-tosyl-N-(4-methyl-3-pentenyl)amino aldehyde benzylimines, which are obtained from alanine, leucine, or phenylalanine methyl esters in five steps, can be cyclized diastereoselectively in the presence of Lewis acids to give 3-amino-2,4-dialkyl-substituted piperidines. The product distribution and diastereoselectivity depends on the type of Lewis acid and nitrogen-protecting group. Benzyl-protected imines give 2-alkyl-3-(benzylamino)-4-isopropenyl piperidines with FeCl(3) and 2-alkyl-3-(benzylidene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Subsequently, the aqueous phase was extracted using diethyl ether. The organic phase was collected, dried with anhydrous sodium sulfate, filtered and the solvent evaporated under vacuum, yielding a colourless oil [17].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the aqueous phase was extracted using diethyl ether. The organic phase was collected, dried with anhydrous sodium sulfate, filtered and the solvent evaporated under vacuum, yielding a colourless oil [17].…”
Section: Methodsmentioning
confidence: 99%
“…20 The effectiveness of the iron salts as Lewis acids was evaluated in the synthesis of piperidine derivatives starting from N-tosylimines. 21 Recently, others 22 and we 23 have shown that FeCl 3 /diorganyl dichalcogenides is an alternative system to the classical protocols to promote cyclization of unsaturated substrates. Besides, the incorporation of an organoselenium or organotellurium group in the structure of molecules has attracted much attention due to their applications in several different reactions, 24 such as selenoxide syn elimination, [2,3]-sigmatropic rearrangement, cyclization, and cross-coupling reactions, as well as their biological properties.…”
Section: ' Introductionmentioning
confidence: 97%
“…Bolm and co-workers have demonstrated that FeCl 3 and 2,2,6,6-tetramethyl-3,5-heptanedione (TMHD) are effective as a catalytic system for an iron-catalyzed intramolecular O-arylation reaction of 2-haloanilines in the synthesis of benzoxazole derivatives . The effectiveness of the iron salts as Lewis acids was evaluated in the synthesis of piperidine derivatives starting from N -tosylimines . Recently, others and we have shown that FeCl 3 /diorganyl dichalcogenides is an alternative system to the classical protocols to promote cyclization of unsaturated substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review on imino ene reactions, only few examples with inverse electron demand have been reported. , Though allylsilanes are well documented to act as electron-rich ene components in ene reactions, the role of allyltrimethylsilane ( 2a ) as an enophile seems to be without precedent.…”
Section: Discussionmentioning
confidence: 99%